What Is Youth Political Participation? Literature Review on Youth Political Participation and Political Attitudes - Weiss, Julia (Frontiers in Political Science, 2020)
Looking at political participation behavior of young adults in contemporary Europe, this paper provides the reader with a map of different terminologies and logics that are used to discuss youth political participation. The existing literature is examined through the lens of five guiding questions: what defines youth political participation? How does youth political participation differ from adult political participation? How do young adults develop political attitudes? How does youth political participation differ across Europe? What methods are being used to analyze youth political participation? For those researching youth political participation for the first time, this paper offers a useful overview of the topic. At the same time, it gives researchers who are already well-informed the opportunity to reflect on the current state of research in this field. Finally, this paper indicates where future research is needed.